Differentiating thyroid nodules parathyroid lesions using 2D-shear-wave elastography: a novel approach for enhanced diagnostic accuracy - Stoian, Dana; Borlea, Andreea; Taban, Laura; Maralescu, Felix-Mihai; Bob, Flaviu; Schiller, Oana; Schiller, Adalbert; Neagoe, Octavian (Frontiers in Endocrinology, 2023)
Differentiating between thyroid and parathyroid lesions by means of ultrasound can be a challenge in some cases. This study explores the diagnostic efficacy of bidimensional shear wave elastography planewave ultrasound (2D SWE PLUS) as an auxiliary technique in distinguishing these superficial structures. We evaluated 86 cases, presenting with concurrent thyroid nodules and hyperparathyroidism, through conventional ultrasound and 2D SWE PLUS, employing an Aixplorer Supersonic Mach30 with a 5-18 MHz linear probe. Statistically significant differences were observed for the elasticity index (EI) between parathyroid and normal thyroid tissue (p<0.0001, U=291), and between parathyroid lesions and thyroid nodules (p<0.0001, U=248.5). An area under the curve (AUC) of 0.961, with an optimal cut-off value of ≤8.9 kPa, was established to effectively distinguish parathyroid tissue from normal thyroid tissue (sensitivity of 91.9%; specificity of 97.5%). Furthermore, an AUC of 0.963 and an optimal cut-off of 9.24 kPa (sensitivity of 94.2%, specificity of 91.1%) were determined for parathyroid vs thyroid lesions. Elasticity values were significantly elevated in the cancer group compared to benign thyroid nodules (p<0.0001). Our findings suggest that 2D SWE PLUS is an effective tool in differentiating between thyroid nodules and parathyroid lesions, enhancing diagnostic performance in neck ultrasonography.